The punitive turn in American life : how the United States learned to fight crime like a war - Sherry, Michael S., 1945- (University of North Carolina Press, 2020)
"In 1965, President Lyndon Johnson insisted that 'the policeman is the frontline soldier in our war against crime,' and police forces, arms makers, policy makers, and crime experts heeded this call to arms, bringing weapons and practices from the arena of war back home. The Punitive Turn in American Life offers a political and cultural history of the ways in which punishment and surveillance have moved to the center of American life and become imbued with militarized language and policies"--